Analisis Ayat Riba dalam Tafsir Al-Azhar Karya Buya Hamka - A. Syafi' AS. (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2018)
This study aims to examine the verses of Riba in Tafsir al-Azhar by Buya Hamka. To capture the contextual meaning that is formed in the Interpretation, the author considers it important to discuss it in this study. This type of research is qualitative descriptive. Considering that this study is about understanding the verses of the Qur'an by analyzing the interpretation of the commentaries, then methodologically this research is categorized as explorative research, meaning understanding the verses of al-Qu'an related to the problem of Riba. The technique of collecting data is documentary study. While the data analysis technique uses critical analytical techniques, with deductive and inductive thinking techniques. The results of the study can be summarized as follows: First; in Surat al-Baqarah: 278, in the word "takwalah and leave it", there is a repetition of the word that makes the sentence ineffective. Therefore, the sentence is changed to "fear Allah and leave the remnants of Riba". Whereas in the phrase "if you truly are believers", there is a waste of words, namely the repetition of words in one sentence. In the opinion of the writer the sentence becomes "if you are truly believers". Second; in Sura Ali Imran: 130, in the opinion of the author the exact word in the phrase "do not eat double usury" is changed to "do not eat usury with multiples". Because the sentence will be an active sentence, and not standard. Whereas in the second sentence, the sentence "so that you may win", is changed to "so that you may win". Because getting is the standard word for the active word "get."